Enfoque de la metodología financiera para el análisis del presupuesto de capital y viabilidad de la alternativa rentable. - Agila Cuenca, Alexandra Beatriz (My University, 2019)
Among the important decisions to be taken by the company are the investments, which are based on a rigorous analysis of accounts, from which profitability will be established on the cost of capital employed, for this reason it is proposed to analyze in a Theoretical and practical investment analysis tools by means of the analysis of a practical case to be able to establish its relevance when making a financial decision, for this purpose the accounting information corresponding to two investment projects has been taken, to the same ones has applied the respective tools of financial analysis as a methodology; In the first project, revenues correspond to 6,019,230.84 for the first year of operation, while for the second, annual revenues will increase by 15% up to 10 years, with these scenarios, project A presented a NPV of $ 10,938,163.98, the IRR 19%, the investment would recover in five years, 9 months, 8 days, the accounting return is equal to 3,356,312,812 and the equivalent annual cost 16,132,348.41, while for the project B, this presented a negative NPV of $ -4,790,158.64, the IRR of 8%, accounting return of 1.65 and annual equivalent cost of 7,064,851.86. The Payback was not necessary in the second project because it would generate losses. After evaluating the two projects, it is concluded that project A is profitable according to all the indicators analyzed, since the investment is recovered, while in the second one it does not.
Entre las decisiones importantes a tomar por la empresa se encuentran las inversiones, las cuales parten de un riguroso análisis de cuentas, de las cuales se establecerá la rentabilidad sobre el costo del capital empleado, es por esta razón que se plantea como objetivo Analizar de manera teórica y práctica las herramientas de análisis de inversiones por medio del análisis de un caso práctico para poder establecer su relevancia al momento de tomar una decisión financiera, para ello se ha tomado la información contable correspondiente a dos proyectos de inversión, a los mismos que se les ha aplicado las respectivas herramientas de análisis financiero como metodología; en el primer proyecto los ingresos corresponden a 6.019.230,84 para el primer año de funcionamiento, mientras que para el segundo, los ingresos anuales tendrán incrementos del 15% hasta los 10 años, con estos escenarios, el proyecto A presentó un VAN de $10.938.163,98, la TIR 19%, la inversión se recuperaría en cinco años, 9 meses, 8 días, el rendimiento contable es igual a 3,356.312,812 y el costo anual equivalente 16.132.348,41, mientras que para el proyecto B, este presentó un VAN negativo de $-4.790.158,64, la TIR del 8%, rendimiento contable 1,65 y costo anual equivalente de 7.064.851,86. El Payback no fue necesario realizarlo en el segundo proyecto por cuanto este generaría pérdidas. Luego de evaluar los dos proyectos se concluye que el proyecto A es rentable de acuerdo a todos los indicadores analizados, ya que se recupera la inversión, mientras que en el segundo no.
Keywords: DECISIONES; INVERSIÓN; CUENTA; PRESUPUESTO DE CAPITAL; RENTABILIDAD